Influence of patient‐specific factors when comparing multifidus fat infiltration between chronic low back pain patients and asymptomatic controls. Issue 4 (14th July 2022) - Ballatori, Alexander M.; Shahrestani, Shane; Nyayapati, Priya; Agarwal, Vibhu; Krug, Roland; Han, Misung; Fields, Aaron J.; O'Neill, Conor; Demir‐Deviren, Sibel; Lotz, Jeffrey C.; Bailey, Jeannie F.
Abstract: Introduction: Many studies have attempted to link multifidus (MF) fat infiltration with muscle quality and chronic low back pain (cLBP), but there is no consensus on these relationships. Methods: In this cross‐sectional cohort study, 39 cLBP patients and 18 asymptomatic controls were included. The MF muscle was manually segmented at each lumbar disc level and fat fraction (FF) measurements were taken from the corresponding advanced imaging water‐fat images. We assessed the distribution patterns of MF fat from L1L2 to L5S1 and compared these patterns between groups. The sample was stratified by age, sex, body mass index (BMI), subject‐reported pain intensity (VAS), and subject‐reported low back pain disability (oswestry disability index, ODI). Results: Older patients had significantly different MF FF distribution patterns compared to older controls ( p  < 0.0001). Male patients had 34.8% higher mean lumbar spine MF FF compared to male controls ( p  = 0.0006), significantly different MF FF distribution patterns ( p  = 0.028), 53.7% higher mean MF FF measurements at L2L3 ( p  = 0.037), and 50.6% higher mean MF FF measurements at L3L4 ( p  = 0.041). Low BMI patients had 29.7% higher mean lumbar spine MF FF compared to low BMI controls ( p  = 0.0077). High BMI patients only had 4% higher mean lumbar spine MF FF compared to high BMI controls ( p  = 0.7933). However, high BMI patients had significantly different MF FF distribution patterns compared to high BMI controls ( p  = 0.0324). Low VAS patients did not significantly differ from the control cohort for any of our outcomes of interest; however, high VAS patients had 24.3% higher mean lumbar spine MF FF values ( p  = 0.0011), significantly different MF FF distribution patterns ( p  < 0.0001), 34.7% higher mean MF FF at L2L3 ( p  = 0.040), and 34.6% higher mean MF FF at L3L4 ( p  = 0.040) compared to the control cohort. Similar trends were observed for ODI. Conclusions: This study suggests that when the presence of paraspinal muscle fat infiltration is not characteristic of an individual's age, sex, and BMI, it may be associated with lower back pain. Abstract : Many studies have attempted to link multifidus fat infiltration with muscle quality and chronic low back pain, but there is no consensus on these relationships. This study suggests that when the presence of fat is not characteristic of an individual's age, sex, and BMI, it may be a back pain risk factor.